Effects of different hormones on germination and callus induction of hemp seeds. Issue 1 (June 2020) - He, Bingqing; Shen, Penglin; Zheng, Hongjuan; Chu, Yi; Guan, Jinqiu; Li, Lan
Abstract: The purpose was to induce and treat hemp seeds and callus, compare the methods to increase the germination rate of hemp seed, obtain suitable disinfectant for hemp seed, and different hormone ratios to promote callus growth. GA3, 6-BA, and IAA were used to induce hemp seed germination, and the effects of different hormones and different concentrations on hemp seed germination were studied. Tissue culture was used to induce hemp seeds to select suitable hemp seeds disinfectant and time; callus was induced by using hemp aseptic seedling leaves. GA3 with a concentration of 20-80mg/L and IAA with a concentration of 20-40mg/L can promote the germination of hemp seeds; the best disinfection method of hemp seeds is: 70% ethanol for 1min + 10% NaClO for 18min; the most the combinations beneficial to callus growth were: 2.0mg/L 6-BA+0.5mg/L NAA. GA3 and low-concentration IAA can promote the germination of hemp seeds; the combination of 70% ethanol and 10% sodium hypochlorite has the best disinfection effect on hemp seeds; 6-BA+NAA can obtain good quality hemp seeds hemp callus.